Do Cerebral Blood Volume and Contrast Transfer Coefficient Predict Prognosis in Human Glioma? - Mills, S.J.; Patankar, T.A.; Haroon, H.A.; Balériaux, D.; Swindell, R.; Jackson, A. (American Journal of Neuroradiology, 2006)
INTRODUCTION: Noninvasive measurements of cerebral blood volume (CBV) and contrast transfer coefficient (Ktrans) have potential benefits in the diagnosis and therapeutic management of adult glioma. This study examines the relationship between CBV, Ktrans, and overall survival.METHODS AND MATERIALS: Twenty-seven adult patients with glioma underwent T1-weighted dynamic contrast-enhanced MR imaging, and parametric maps of CBV and Ktrans were calculated. The relationship of histologic grade, CBV, Ktrans, age, sex, surgical resection, and use of adjuvant therapy to survival were analyzed by using the logrank method and Cox regression analysis. The Kaplan-Meier method for displaying survival curves was used. The relationship of factors such as comorbidity, elevated intracranial pressure, size of nonenhancing tumor, and peritumoral edema were not considered.RESULTS: Both CBV (P < .01) and Ktrans (P < .01) show a significant relationship to histologic grade. CBV (P = .004), Ktrans (P = .008), and histologic grade (P < .001) all demonstrate a significant association with patient survival when analyzed individually. Cox regression analysis identified only histologic grade (P < .01) and Ktrans (P < .05) as independent significant prognostic indicators. Examination of survival data from high-grade (III and IV) tumors demonstrated a linear relationship between Ktrans and patient survival (P < .01).CONCLUSION: This study suggests a direct relationship between Ktrans and length of survival in high-grade gliomas, which could be of clinical importance. CBV relates directly to histologic grade but provides no independent prognostic information over and above that provided by grade. Further large prospective studies should be planned to test whether this observation holds true.